Peningkatan Peran Kader Perempuan Melalui Program Pengolahan Biofarmaka Berbasis Komunitas di Desa Bulu Kecamatan Berbek Kabupaten Nganjuk - Niken Ristianah; Idam Mustofa; Abdul Hafidz Miftahuddin (Janaka, Jurnal Pengabdian Masyarakat, 2021)
The problem experienced by the people of Bulu Village lies in the lack of skills in processing bio-pharmaceutical plants into products of economic value. The emergence of the initiation of female leaders to empower the assets and potential of bio-farm plants is very much needed. Through a humanistic approach, it is possible for the participatory researchers and the PKK Bulu Village community to plan, conduct and evaluate research results. This is done as an effort to increase the role of female cadres through a community-based bio-pharmaceutical processing program in Bulu Village. The method of this community assistance program is service learning. Researchers conducted guidance to the female cadres of Bulu Village to be able to share knowledge in processing bio-farm plants into instant herbal medicine powder. Researchers empower students to share their knowledge with Bulu Village PKK members with stakeholder support. Activities carried out in two stages, namely the development of knowledge sharing programs and mainstreaming of knowledge sharing programs. The results of the mentoring show that the development of community potential is identified with the efforts of Bulu Village women cadres individually, institutions and systems to increase the potential of their members.